Unmanned aerial vehicle-aided cooperative regenerative relaying network under various environments - Thanh-Luan Nguyen; Duy-Hung Ha; Phu Tran Tin; Hien Dinh Cong (International Journal of Electrical and Computer Engineering (IJECE), 2021)
This paper studies a cooperative relay network that comprises an unmanned aerial vehicle (UAV) enabling amplify-and-forward (AF) and power splitting (PS) based energy harvesting. The considered system can be constructed in various environments such as suburban, urban, dense urban, and high-rise urban where the air-to-ground channels are model by a mixture of Rayleigh and Nakagami-m fading. Then, outage probability and ergodic capacity are provided under different environment-based parameters. Optimal PS ratios are also provided under normal and high transmit power regimes. Finally, the accuracy of the analytical results is validated through Monte Carlo methods.